In vitro Regeneration of the Medicinal Herb of Nilgiri shola, Acmella calva L. from Leaf Derived Callus (Plant Tissue Culture and Biotechnology, 2009)
Callus culture was initiated from leaf discs on MS supplemented with BAP, NAA and Kn. The highest frequency (95%) of organogenic callus induction was observed in MS containing BAP at 3.0 mg/l and NAA at 0.3 mg/l. Development of adventitious shoots occurred when the calli were subcultured on MS supplemented with BAP alone at the rate of 3.0 mg/l (80%) and BAP with NAA at the rate of 3.0 and 0.3 mg/l, respectively (95%) and BAP with Kn at the rate of 3.0 and 0.3 mg/l, respectively (70%). The root initiation and the rate of growth were higher in the basal medium containing BAP at 3.0 and 2.5 mg/l. The plantlets were establish successfully in the hardening medium composed by coir pith and soil (1 : 1).Key words: Acmella calva, Leaf derived callus, Nilgiris, India Plant Tissue Cult. & Biotech. 17(2): 109-114, 2007 DOI: 10.3329/ptcb.v17i2.2566